Advancing Mandibular Reconstruction for Ameloblastoma: A Literature Review on the Role of Virtual Surgical Planning and Custom 3D Implants - Bryan Julio Hasim; How Kim Chuan; Susanna Halim (Jurnal Penelitian Pendidikan IPA, 2025)
Ameloblastoma is a benign yet locally aggressive odontogenic tumor often requiring extensive mandibular resection, leading to significant anatomical and functional deficits. Traditional reconstruction techniques frequently fall short in restoring facial symmetry, occlusal function, and aesthetic outcomes. Virtual surgical planning (VSP) has revolutionized mandibular reconstruction by enabling digitally guided, patient-specific workflows. This literature review evaluates the integration of VSP in managing ameloblastoma-related mandibular defects, particularly with custom titanium implants, lattice structures, and artificial intelligence. Evidence suggests that VSP enhances surgical precision, shortens operative time, and improves aesthetic and functional outcomes. The convergence of virtual planning, additive manufacturing, and AI underscores VSP's emerging status as the gold standard in maxillofacial oncologic surgery.